1997
DOI: 10.1021/np9700331
|View full text |Cite
|
Sign up to set email alerts
|

New Terpenylated Dihydrochalcone Derivatives Isolated from Mitrella kentii

Abstract: From the EtOH extract of the stem bark of Mitrella kentii (Annonaceae), two new terpenylated dihydrochalcones were isolated, namely (-)-neolinderatin ( 1) and (-)-linderatin (2), together with known compounds 2′,6′-dihydroxy-4′-methoxydihydrochalcone and (+)-catechin. Their structures were elucidated by means of combined analytical methods including HREIMS, DC, 1D, and 2D NMR spectroscopies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Experimentally, the plant showed anti-inflammatory activity [10]. Previous chemical studies on M. kentii resulted in the isolation of isoquinoline alkaloids [11], terpenylated dihydrochalcones [12] and four other benzoic acids [10]. As a continuation of our research for biologically active compounds for the treatment of gastric ulcer from the Malaysian flora, a hexane extract of the bark of this plant was selected for phytochemical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the plant showed anti-inflammatory activity [10]. Previous chemical studies on M. kentii resulted in the isolation of isoquinoline alkaloids [11], terpenylated dihydrochalcones [12] and four other benzoic acids [10]. As a continuation of our research for biologically active compounds for the treatment of gastric ulcer from the Malaysian flora, a hexane extract of the bark of this plant was selected for phytochemical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…While most DHCs found in nature are derived from phloretin, some plants, such as Uvaria angolensis (Hufford and Oguntimein, 1980) or Mitrella kentia (Benosman et al, 1997), accumulate also DHC structures lacking the 4-hydroxy group. This means they are most likely derived from pinocembrin DHC and are produced by CHS from dihydrocinnamoyl-CoA and three units of malonyl-CoA.…”
Section: Resultsmentioning
confidence: 99%
“…These observations together with the CH 2 and CH 1 H, 1 H-correlation shown in Fig. 3 suggested that 3 is a 3-substituted menthene derivative with a freely rotating side-chain [10] [11]. The olefinic H-atoms at d(H) 7.38 (HÀC(7)) and 6.77 (HÀC(6)) correlated with a quaternary C-atom at d(C) 158.8 (C(5)) and the aromatic C-atom at d(C) 137.2 (C(8)).…”
Section: (¼ (2e)-1-{24-dihydroxy-3-[(1s2e5s)-5-hydroxy-17-bis(4-hmentioning
confidence: 99%